Formation of sociocultural competence of students in the process of learning a foreign language as the actual pedagogical problem - Щербина, Ілона Юріївна (Pedagogy of Higher and Secondary Education, 2013)
Shcherbina І. Yu. Formation of sociocultural competence of students in the process of learning a foreign language as the actual pedagogical problem. The article considers the nature of socio-cultural competence as a component of pupils’ foreign language communicative competence; elucidates its structure and points out the major components, identifies key approaches to forming socio-cultural competence of students in the process of foreign language learning.